Antioxidant activity and chemical characterization of extracts from the Genus Hymenaea - Figueiredo, Patrícia Aparecida [UNESP]; Spera, Kamille Daleck [UNESP]; Gomes, Amanda da Costa [UNESP]; Dokkedal, Anne Lígia [UNESP]; Saldanha, Luiz Leonardo [UNESP]; Ximenes, Valdecir Farias [UNESP]; Silva, Luciana Pereira; da Silva, Regildo Márcio Gonçalves [UNESP] (Science Alert, 2016)
Background and Objective: The genus Hymenaea August 6, 20l6(Fabaceae, Caesalpinioideae) is comprised of 14 species, 12 of which occur in several Brazilian regions commonly known as “Jatoba”. Several scientific studies of these species are being conducted to demonstrate their potential for pharmaceutical and food industries. Methodology: This study assessed antioxidant activity and sun protection by several parts of two endemic medicinal plants from Brazil, Hymenaea courbarii and Hymenaea stigonocarpa, through DPPH, FRAP and ORAC-FL assays. Fractionation of 70% ethanolic seed extract from H. courbarH was performed. The flavonoids profile by HPLC-PAD was performed with 70% ethanol fractions that showed better results for antioxidants tests and total phenols content. Results: All extracts showed antioxidant activity and high phenolic compound content, except the pulp extract. The fraction ethyl acetate methanol (EAM) 70:30 showed better results for DPPH, FRAP and total phenolic content (72.21±1.08%, 3029.97±09J8 µM TE g-1 extract and 49l.56±02.62 mg GAE g-1 of dry extract, respectively). The HPLC-PAD analysis revealed a spectrum with typical absorption bands of flavonoids for the fraction ethyl acetate:methanol 70:30. The results of this study indicate that the 70% ethanol extract from seeds of the specie H. courbarH and its fraction EAM 70:30 showed high antioxidant activity, as well as the presence of phenolic compounds. Conclusion: These results suggest that H. courbarHshould be further explored with a focus on use in cosmetic, pharmaceutical and food formulations.
Keywords: FRAP; Hymenaea courbarii; Hymenaea stigonocarpa; ORAC